Administrasi Pendidikan: Integrasi Landasan Teoritis Dalam Implementasi Pengelolaan Sekolah Berkualitas: Educational Administration: Integration of Theoretical Foundations in the Implementation of Quality School Management - Emilda Yuliastuti (Qudwah: Journal of Islamic Education, 2026)
Educational administration can be understood as a series of planned and ongoing activities in managing various educational resources in an integrated manner to achieve effective, efficient, and quality learning objectives. This study aims to comprehensively review the basic concepts, functions, and main elements of educational administration, while also mapping the various challenges that arise in the dynamics of contemporary education. The method used in this research is a literature study by analyzing a number of relevant scientific literature, both in the form of books and journal articles that discuss the theory and practice of educational administration. The results of the study indicate that educational administration has a strategic position in improving the quality and effectiveness of education delivery. This is reflected in the systematic implementation of managerial functions that include planning, organizing, directing, and monitoring. The main components of educational administration include the management of students, teaching and educational staff, curriculum, facilities and infrastructure, financing, and strengthening the relationship between schools and the community. In facing the era of globalization and the acceleration of digital transformation, educational administration is faced with various challenges, including demands for quality improvement, the dynamics of educational policies, limited resources, and increasingly rapid technological developments. Therefore, the implementation of innovative, adaptive, and information technology-based educational management is an important strategy to create educational institutions that are transparent, responsive to change, and have sustainable competitiveness.